2022
DOI: 10.3390/cancers14020368
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Active Surveillance for Prostate Cancer in a Single-Center Cohort: Favorable Outcomes after Transurethral Resection of the Prostate

Abstract: Objective: To report the outcomes of active surveillance (AS) for low-risk prostate cancer (PCa) in a single-center cohort. Patients and Methods: This is a prospective, single-center, observational study. The cohort included all patients who underwent AS for PCa between December 1999 and December 2020 at our institution. Follow-up appointments (FU) ended in February 2021. Results: A total of 413 men were enrolled in the study, and 391 had at least one FU. Of those who followed up, 267 had PCa diagnosed by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“… 21 In comparison to men who underwent TURP, men diagnosed by TRUS guided biopsy had significantly higher reclassification, defined as pathological progression of tumor, (25% at 3.6 years vs. 25% at 11.2 years) while on active surveillance ( p < .001). 21 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“… 21 In comparison to men who underwent TURP, men diagnosed by TRUS guided biopsy had significantly higher reclassification, defined as pathological progression of tumor, (25% at 3.6 years vs. 25% at 11.2 years) while on active surveillance ( p < .001). 21 …”
Section: Discussionmentioning
confidence: 86%
“…21 In comparison to men who underwent TURP, men diagnosed by TRUS guided biopsy had significantly higher reclassification, defined as pathological progression of tumor, (25% at 3.6 years vs. 25% at 11.2 years) while on active surveillance (p < .001). 21 In patients who undergo a surgical procedure for BPH, incidental prostate cancer may be found in up to 12% of patients. 22,23 Many of these patients have low-risk disease and can be managed with active surveillance or watchful waiting.…”
Section: Discussionmentioning
confidence: 86%
“…AS should be considered as the treatment of choice for the majority of PCa patients with localized disease, as it does not compromise survival while significantly improving quality of life [ 1 , 3 ]. However, interventional methods of treatment are not exclusive but complementary, as approximately half of the patients will eventually receive active treatment [ 1 , 25 ], and some will decline AS to start off with. In general, there are three ultra-short radiotherapy modalities that can be considered in such setting, including low-dose-rate brachytherapy (LDR-BT), high-dose-rate brachytherapy (HDR-BT), and UHRT.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional therapies such as radical prostatectomy (RPE) or radiation are recommended for localized tumors in the intermediate-and high-risk groups [4]. Recent long-term outcomes showed that active surveillance (AS) is a safe option for localized low-risk tumors, aiming to reduce Diagnostics 2022, 12, 1146. https://doi.org/10.3390/diagnostics12051146 https://www.mdpi.com/journal/diagnostics overtreatment and negative side effects of interventional treatments [5]. These patients follow up on a routine schedule with regular PSA measurements, digital rectal examinations and prostate biopsies to determine whether further AS is warranted or a progression of the tumor disease requiring interventional therapy is present.…”
Section: Introductionmentioning
confidence: 99%